Arkema unveils impact modifier for thermoset applications; achieves record EBITDA in 2016. Issue 5 (May 2017) - Unknown
Abstract : French firm Arkema has introduced Clearstrength® XT100, a methacrylate-butadiene-styrene (MBS) core/shell impact modifier designed to satisfy the most demanding technical requirements of thermoset applications, such as structural adhesives and high-performance composites. The new product was among the composites innovations presented by the company at the JEC World 2017 tradeshow in Paris.